2019
DOI: 10.1210/clinem/dgz303
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Analysis of Brain MRI Parameter Dynamics in Young Patients With Cushing Syndrome—A Case-Control Study

Abstract: Background Young patients with Cushing Syndrome (CS) may develop cognitive and behavioral alterations during disease course. Methods To investigate the effects of CS on the brain, we analyzed consecutive MRI scans of patients with (n = 29) versus without CS (n = 8). Multiple brain compartments were processed for total and gray/white matter (GM/WM) volumes and intensities, and cortical volume, thickness, and surface area. Dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In the AdKO 2.0 brains, volumetric decreases were prominent in white matter areas, such as the corpus callosum and cingulate cingulum. In human studies, patients show smaller absolute volumes of white matter ( Jiang et al, 2019 ; Tirosh et al, 2020 ), as well as reduced fractional anisotropy and increased mean diffusivity, which indicate white matter deterioration ( Pires et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the AdKO 2.0 brains, volumetric decreases were prominent in white matter areas, such as the corpus callosum and cingulate cingulum. In human studies, patients show smaller absolute volumes of white matter ( Jiang et al, 2019 ; Tirosh et al, 2020 ), as well as reduced fractional anisotropy and increased mean diffusivity, which indicate white matter deterioration ( Pires et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, significant and positive correlations were observed between GMVs in these subregions and remission time in short-term-remitted CD patients. Previous studies demonstrated not only partially reversible GMV reductions in particular brain subregions, such as the hippocampus ( 8 , 28 ), but also similar partial reversibility in other brain subregions and in the whole brain ( 17 , 29 ). Thus, it is reasonable to assume that partial reversibility of GMVs could be found, not only in particular brain subregions but also in most brain subregions of remitted CD patients.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have reported a reduction in cortical thickness in patients with stress-related disorders such as generalized and social anxiety disorder 25 , 26 bipolar disorder 27 , 28 , and major depressive disorder 29 , 30 . Two earlier studies investigated cortical thickness in CS patients and HCs: the first found no differences in cortical thickness 31 and the second reported increased cortical thickness in the lateral orbitofrontal and superior frontal cortex in children with CS in compared to HCs, however this study did not adjust for multiple comparisons 32 .…”
Section: Introductionmentioning
confidence: 82%
“…These findings are not in line with two previous studies investigating cortical thickness in CS patients. One study did not identify any differences in cortical thickness 31 , and the second study identified increased cortical thickness in the lateral orbitofrontal-and superior frontal cortex in children with CS in compared to HCs but did not adjust for multiple comparisons 32 . As the differences found in these areas appear to be marginal, it is unlikely that these effects would have persisted after correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation